2017
DOI: 10.1371/journal.pone.0181406
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen reduction through additive-free short-wave UV light irradiation retains the optimal efficacy of human platelet lysate for the expansion of human bone marrow mesenchymal stem cells

Abstract: BackgroundWe recently developed and characterized a standardized and clinical grade human Platelet Lysate (hPL) that constitutes an advantageous substitute for fetal bovine serum (FBS) for human mesenchymal stem cell (hMSC) expansion required in cell therapy procedures, avoiding xenogenic risks (virological and immunological) and ethical issues. Because of the progressive use of pathogen-reduced (PR) labile blood components, and the requirement of ensuring the viral safety of raw materials for cell therapy pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 72 publications
(99 reference statements)
1
32
0
Order By: Relevance
“…Moreover, the interaction of BM‐MSCs versus PBMNCs showed an inhibition of PBMNC proliferation. This inhibition was described in previous studies at the 1:20 ratio but is similar to ours at the 1:10 ratio. This inhibition was less with DVI‐HPL.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the interaction of BM‐MSCs versus PBMNCs showed an inhibition of PBMNC proliferation. This inhibition was described in previous studies at the 1:20 ratio but is similar to ours at the 1:10 ratio. This inhibition was less with DVI‐HPL.…”
Section: Discussionsupporting
confidence: 92%
“…In terms of content, one major difference between the two human nutritive substitutes used in the present study is the presence in hPL of plasma fibrinogen and of heparin, which is required to avoid gelation of the medium. In light of previous studies suggesting that the heparin concentration may affect stem cell proliferation and/or differentiation [ 70 ], we investigated the effects of heparin on myogenic commitment in MuStem cells. hMuStem cells HS were cultured in the presence of increasing doses of heparin (0.5–5 IU/ml), with the highest dose corresponding to that found in hPL-GM.…”
Section: Resultsmentioning
confidence: 99%
“…The effects of pathogen inactivation on growth factor stability during storage have previously been studied. It was demonstrated that UVC treatment of platelet concentrates had no effect on concentrations of EGF, FGF-2, PDGF-AB, VEGF, or insulin-like growth factor (IGF) [35]. In a study specifically conducted on the INTERCEPT™ Blood System…”
Section: Discussionmentioning
confidence: 99%